Censurae Librorum - Wysłucha, Kamila (Polskie Towarzystwo Filologiczne, 2018)
Arystoksenos z Tarentu, Harmonika, przekład, wstęp i komentarz Anna Maciejewska [Aristoxenus of Tarent, Harmonics, Translated with an Introduction and Commentary by Anna Maciejewska], Łódź: Wydawnictwo Uniwersytetu Łódzkiego, 2015, L + 61 pp., ISBN 978-83-7969-920-9.
Keywords: censurae librorum